2017
DOI: 10.1186/s12943-017-0713-9
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic role of the In1-ghrelin splicing variant in prostate cancer aggressiveness

Abstract: BackgroundThe Ghrelin-system is a complex, pleiotropic family composed of several peptides, including native-ghrelin and its In1-ghrelin splicing variant, and receptors (GHSR 1a/b), which are dysregulated in various endocrine-related tumors, where they associate to pathophysiological features, but the presence, functional role, and mechanisms of actions of In1-ghrelin splicing variant in prostate-cancer (PCa), is completely unexplored. Herein, we aimed to determine the presence of key ghrelin-system components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 44 publications
3
68
0
Order By: Relevance
“…When viewed as a whole, the results of the present manuscript indicating that GOAT levels are markedly elevated in Sig PCa and are associated to aggressiveness features in PCa (i.e. GS and presence of metastasis), together with the previous results showing a strong correlation of GOAT levels with In1‐ghrelin variant levels in PCa, invite to suggest that GOAT enzyme and In1‐ghrelin variants could be functionally linked in PCa, where In1‐ghrelin variant might be the primary target of GOAT, and that an autocrine/paracrine circuit involving these two components of the ghrelin system may possibly operate in PCa to increase the aggressiveness features of PCa cells, which set the stage for future investigations.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…When viewed as a whole, the results of the present manuscript indicating that GOAT levels are markedly elevated in Sig PCa and are associated to aggressiveness features in PCa (i.e. GS and presence of metastasis), together with the previous results showing a strong correlation of GOAT levels with In1‐ghrelin variant levels in PCa, invite to suggest that GOAT enzyme and In1‐ghrelin variants could be functionally linked in PCa, where In1‐ghrelin variant might be the primary target of GOAT, and that an autocrine/paracrine circuit involving these two components of the ghrelin system may possibly operate in PCa to increase the aggressiveness features of PCa cells, which set the stage for future investigations.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, plasma GOAT levels tended to be associated with an earlier diagnosis of CRPC, which might also indicate that this enzyme may serve to develop future therapeutic target for PCa. In line with this, we have recently demonstrated that GOAT enzyme is positively correlated in PCa with the levels of the In1‐ghrelin splicing variant, but not with those of native‐ghrelin, wherein the presence of In1‐ghrelin variant drastically increased the aggressiveness features of PCa, acting as a true oncogene in this pathology . In fact, this previous study demonstrated that In1‐ghrelin silencing diminished the aggressiveness of PCa cells (e.g.…”
Section: Discussionsupporting
confidence: 56%
“…DU145 and LNCaP cell lines were obtained from American Type Culture Collection (ATCC; Manassas, VA, USA), cultured according to the manufacturer's instructions, validated by analysis of short tandem repeats sequences using GenePrint 10 System (Promega, Barcelona, Spain) and checked for mycoplasma contamination by PCR as previously reported [8,16]. DU145 cells were selected for functional in vitro and in vivo analyses based on its high expression levels of In1-ghrelin, the main oncogenic element of the ghrelin axis in prostate cancer, which is also a putative target of GOAT [8]. The GOAT inhibitor "GO-CoA-Tat" (032-37; Phoenix Biotech, Burlingame, CA, USA) was resuspended in water and used at 10 µM since this dose has been previously reported to be effective reducing GOAT activity [17].…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…In this regard, a ghrelin system has emerged as a pivotal regulatory axis in PCa pathophysiology [5,6], as well as a source of potential PCa biomarkers, since certain peptides derived from this pleiotropic system (i.e., native ghrelin, In1-ghrelin splice variant) are secreted by PCa cells and associated to PCa aggressiveness [7,8]. Ghrelin axis is controlled, at least in part, by the Ghrelin O-Acyl Transferase (GOAT or MBOAT4), an enzyme involved in the acylation and, thus, activation of ghrelin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation